Measurement of the top-quark mass in all-jets [Formula: see text] events in pp collisions at [Formula: see text] TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V M; et al. (The European physical journal. C, Particles and fields, 2014)
The mass of the top quark is measured using a sample of [Formula: see text] candidate events with at least six jets in the final state. The sample is selected from data collected with the CMS detector in pp collisions at [Formula: see text] TeV in 2011 and corresponds to an integrated luminosity of 3.54 [Formula: see text]. The mass is reconstructed for each event employing a kinematic fit of the jets to a [Formula: see text] hypothesis. The top-quark mass is measured to be [Formula: see text] GeV. A combination with previously published measurements in other decay modes by CMS yields a mass of [Formula: see text] GeV.